The Cycle of Exclusion in Local Print News: How News Content Reflects and Reinforces Patriarchy - (:unkn) unknown (My University, 2017)
Print news has been relied upon as a source of information for centuries. Despite recent strides towards gender equality, women are persistently marginalized in news content and newsrooms. This thesis analyzed over 950 staff-written Milwaukee Journal Sentinel stories and conducted 19 interviews with both men and women staff reporters and editors to examine how patriarchy might infiltrate local print news. I analyzed how women and men authors, sources and subjects are included or excluded from the news. Furthermore, this thesis examines the gendered division of labor within the newsroom.
Keywords: Gender; Journalism; News